Material Removal Rate Prediction for Sapphire Double-Sided CMP Based on RSM-SVM. (1st August 2022) - Li, Zhongyang; Deng, Zhaohui; Ge, Jimin; Zhuo, Rongjing; Wan, Linlin
Abstract : As a crucial substrate material for optoelectronic materials, sapphire has important applications in both military and civilian fields. In order to achieve the final processing quality of sapphire substrate materials, double-sided chemical mechanical polishing (DS-CMP) is a necessary process, which is also a guarantee for the preparation of high-end LED chips. In this article, the sapphire DS-CMP processing plan based on the Box-Behnken design is obtained and experimented. Then, a hybrid approach of response surface method (RSM) and support vector machines (SVM) algorithm is established as the material removal rate (MRR) prediction model for sapphire DS-CMP. Furthermore, the material removal process of sapphire DS-CMP, the influence of response variables on the MRR of sapphire DS-CMP, and the prediction results of RSM-SVM on sapphire DS-CMP are analyzed respectively. From the experimental results, the maximum MRR obtained is 387.59 nm min −1, which is more than 6 times the reported MRR of single-sided CMP under similar process parameters. The mean square error of predicted value through RSM-SVM is basically around ±10% of the experimental value, which possess satisfied validity for the MRR prediction of sapphire DS-CMP. Finally, both top and bottom surface quality of sapphire wafers after DS-CMP processing was investigated.